2017
DOI: 10.1111/are.13287
|View full text |Cite
|
Sign up to set email alerts
|

Geosmin depuration from European eel (Anguilla anguilla ) is not affected by the water renewal rate of depuration tanks

Abstract: This study established that geosmin depuration from European eel is not affected by the water renewal rate of depuration tanks. A general fish bioaccumulation model extended with terms that account for effects of tank water renewal rate and system losses of chemicals, predicted strong effects of the water renewal rate of depuration tanks on geosmin depuration from European eel. Model predictions were validated in a depuration experiment with geosmin-loaded European eel (n = 95) with a mean (SD) individual weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
1
19
1
Order By: Relevance
“…In closed systems, the water renewal rate is the limiting factor for GSM depuration. However, Schram et al () reported that they did not detect any effect of tank water renewal of an eel ( Anguilla anguilla ) RAS farm on the concentration of GSM in the depuration tank.…”
Section: Removal Of Off‐flavours In Rasmentioning
confidence: 99%
See 4 more Smart Citations
“…In closed systems, the water renewal rate is the limiting factor for GSM depuration. However, Schram et al () reported that they did not detect any effect of tank water renewal of an eel ( Anguilla anguilla ) RAS farm on the concentration of GSM in the depuration tank.…”
Section: Removal Of Off‐flavours In Rasmentioning
confidence: 99%
“…In the case of GSM and MIB (K ow 3.57 and 3.31), the main uptake route is via the gills (From & Hørlyck, ), the gastrointestinal tract being a less important route (Howgate, ; Streit, ). Geosmin and MIB are accumulated rapidly (Johnsen & Lloyd, ; Johnsen, Lloyd, Vinyard, & Dionigi, ) in the body lipids of fish, which, it is assumed, proceeds passively, is reversible and concentration‐driven (Schram et al, ). The chemicals can diffuse freely in and out of fish via the gills, depending on the fugacity gradient between water and fish until equilibrium is reached (Howgate, ).…”
Section: Removal Of Off‐flavours In Rasmentioning
confidence: 99%
See 3 more Smart Citations